Mapeamento e engenharia genética de leveduras industriais para fermentação de milho - Sousa, Lara Isensee Saboya, 1998- (2024)
Orientadores: Gonçalo Amarante Guimarães Pereira, Fellipe da Silveira Bezerra de Mello